A Chromosome-Scale Genome of Trametes versicolor and Transcriptome-Based Screening for Light-Induced Genes That Promote Triterpene Biosynthesis - Yang Yang; Xuebo Hu (Journal of Fungi)
Trametes versicolor is an important fungus with medicinal properties and a significant role in lignocellulose degradation. In this study, we constructed a high-quality chromosome-level genome of T. versicolor using Illumina, PacBio HiFi, and Hi-C sequencing technologies. The assembled genome is 47.42 Mb in size and contains 13,307 protein-coding genes. BUSCO analysis revealed genome and gene completeness results of 95.80% and 95.90%, respectively. Phylogenetic analysis showed that T. versicolor is most closely related to T. pubescens, followed by T. cinnabarina and T. coccinea. Comparative genomic analysis identified 266 syntenic blocks between T. versicolor and Wolfiporia cocos, indicating a conserved evolutionary pattern between the two species. Gene family analysis highlighted the expansion and contraction of genes in functional categories related to the biosynthesis of secondary metabolites, including several T. versicolor-specific genes. Key genes involved in lignocellulose degradation and triterpene production were identified within the CAZyme and CYP450 gene families. Transcriptomic analysis under dark and light conditions revealed significant changes in the expression of genes related to secondary metabolism, suggesting that light signals regulate metabolic pathways. A total of 2577 transporter proteins and 2582 membrane proteins were identified and mapped in the T. versicolor genome, and 33 secondary metabolite gene clusters were identified, including two light-sensitive triterpene biosynthesis clusters. This study offers a comprehensive genomic resource for further investigation into the functional genomics, metabolic regulation, and triterpene biosynthesis of T. versicolor, providing valuable insights into fungal evolution and biotechnological applications.